The EURO-FORTA (Fit fOR The Aged) list: international consensus validation of a clinical tool for improved drug treatment in older people - Pazan, Farhad; Weiß, Christel; Wehling, Martin (Drugs & aging, 2018)
Background: Drug treatment of older people is still potentially inappropriate in many cases as multimorbidity and related polypharmacy are highly prevalent. To increase the quality of drug treatment in older people, the FORTA (Fit fOR The Aged) List (first version 2012) was developed in a Delphi consensus procedure and updated (FORTA2015) by 21 experts from Germany and Austria. It has been validated in a randomized, controlled, prospective trial demonstrating significant improvement in the quality of drug treatment and clinical endpoints (VALFORTA). Methods: Based on these results, Delphi consensus validations (two rounds) of country/region-specific FORTA Lists were conducted in the UK/Ireland, France, Poland, Italy, Spain, the Nordic countries and The Netherlands. An algorithm based on geriatric/pharmacologic expertise, publications and professional position was used to find experts in the field. Results: Forty-seven experts agreed to participate in the Delphi process (return rate of 97.9%). For each country/region, the overall mean consensus coefficient (deviation from the initiator proposal) was > 0.9. FORTA Lists from six countries/regions with a minimum of four participating experts (excluding The Netherlands) plus the original FORTA List were collated into the EURO-FORTA List containing 264 items in 26 main indication groups. Two drugs had to be added to the proposed items, as proposed by at least four countries/regions; none had to be removed. Conclusion: This project produced seven new country/region-specific FORTA Lists, as well as the overarching EURO-FORTA List showing a high consensual level based on a broader expert base. EURO-FORTA should help to spread the FORTA approach and improve geriatric pharmacotherapy internationally.
Gesehen am 17.09.2019